2019
DOI: 10.14507/epaa.27.4441
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of college and career readiness emphasis in ESSA state accountability plans

Abstract: This study examined the extent and manner in which college and career readiness (CCR) is emphasized in Every Student Succeeds Act (ESSA) state accountability plans. We analyzed 52 plans (50 states, DC, Puerto Rico) using frameworks developed by Cook-Harvey, Darling-Hammond, Lam, Mercer, and Roc (2016) and Dowd and Bensimon (2015). Findings disclose significant variation, with CCR featuring prominently in some plans and receiving cursory mention in others. Most states identified CCR components as part of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It is, however, a more complex measure. It typically includes a range of individual metrics covering such areas as academic courses completed, ACT/SAT participation and scores, availability and completion of Advanced Placement courses, international baccalaureate participation and scores, career training and certificates, and various other practices that might prepare a student for post-secondary success in college, career, or military activities (Achieve, 2018(Achieve, , 2019Hackman et al, 2019).…”
Section: Discussion: Indicator Weightsmentioning
confidence: 99%
“…It is, however, a more complex measure. It typically includes a range of individual metrics covering such areas as academic courses completed, ACT/SAT participation and scores, availability and completion of Advanced Placement courses, international baccalaureate participation and scores, career training and certificates, and various other practices that might prepare a student for post-secondary success in college, career, or military activities (Achieve, 2018(Achieve, , 2019Hackman et al, 2019).…”
Section: Discussion: Indicator Weightsmentioning
confidence: 99%
“…In their analysis of college and career readiness (CCR) standards in Illinois, Malin et al (2017) found distinct differences in the vision of what constitutes CCR at the state and federal levels and concluded that such flexibility “portends wide variation in emphasis toward, and accountability for, long-standing equity issues” (p. 810). Further, in their analysis of all 52 approved state ESSA plans, Hackmann et al (2019) found that most states identified CCR as part of their school quality or student success (SQSS) indicators in their accountability systems, but very few developed plans to address inequities, instead adopting a colorblind approach to address CCR for all students rather than focusing on subgroups of students.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…Planning is a strategy used by federal and state policymakers as well as accrediting agencies to prompt improvement of institutional and student outcomes (Hackman et al, 2019;Sun et al, 2017). Planning offers institutional leaders the opportunity to reflect on and revise existing practice, create a course of action for future success, and monitor progress on impact (Green, 2017;Redding & Searby, 2020).…”
Section: Planning Efforts In Educationmentioning
confidence: 99%
“…An accountability approach to planning focuses on performance and progress with the goal of improving student and institutional outcomes. Many of these plans are used to hold schools responsible for past performance and for detailing ways to increase academic achievement for all students (Hackman et al, 2019). Scholars also associate accountability efforts with the need to "turn-around" or support "struggling" schools (Strunk et al, 2016).…”
Section: Planning Efforts In Educationmentioning
confidence: 99%